PAPANICOLAOU: FROTIS SIN COMPONENTE ENDOCERVICAL - Luisa Sánchez L; Andrea Rojas S; María Riquelme D; Orlando Quezada P; Fanny López A (Permanyer, 2008)
Objetivo: Evaluar la calidad de la toma del Papanicolaou (PAP) informados como frotis menos que óptimos (I-G7) en 2002 (sin componente endocervical), y conocer el seguimiento de las mujeres en el resultado del PAP siguiente 2003 - 2005. Método: Estudio descriptivo, cuantitativo y de seguimiento de cohorte. Se incluyó el resultado de 42.281 frotis de citología cervical, que correspondieron al universo de los PAP recolectados en 2002 en los consultorios de Atención Primaria de Salud del Área Metropolitana Sur de Santiago. Posteriormente, fueron seleccionados todos los PAP I-G7 de una cohorte de mujeres entre 25 a 50 años y sin antecedentes de lesiones o procedimientos cervicales. Resultados: El estudio evidenció que la toma de muestra de PAP en los consultorios, a excepción de 2 establecimientos, está dentro de los índices de calidad preconizados por el Ministerio de Salud. En el seguimiento de la cohorte de mujeres con PAP I-G7, se pesquisó la existencia de lesión cervical en un 3,38% de las mujeres que se repitieron el examen. Conclusión: Los PAP informados como frotis sin componente endocervical constituyen una categoría de riesgo, ya que el seguimiento de esas mujeres que se repitieron el examen de PAP en un período de hasta 3 años se detectaron lesiones cervicales de alto grado. Objective: To evaluate the quality of sampling cervical cytological through the Papanicolaou (PAP) reported as less than optimal smears (I-G7), i.e. without endocervical component in theyear2002. To know the follow up of a women cohort, in the next PAP smears between 2003 to 2005. Method: Descriptive study, quantitative and follow up of a cohort. It included the results from 42.281 smears cervical cytological according to the national classification, which corresponded to the universe of PAP collected in the 2002 at clinics Primary Health Care in the South Metropolitan Area of Santiago. All PAP with outcome I-G7 from a cohort of women between 25 to 50 years and without history of injury or cervical procedures were selected. In addition, it was identified the clinics provenance. Results: The study showed that the sample of PAP in the clinics, with the exception of 2 establishments, it is within the quality indices expected by the Ministry of Health. In the follow-up of the cohort of women with PAP I-G7 was detected the existence of a cervical lesion 3.38% of the women who were repeated this smear. Conclusion: PAP smears reported as without component endocervical constitute a category of risk, since the follow up the women who were repeated this PAP smear over a period of up to 3 years high-grade cervical lesions were detected.